Fetal middle cerebral artery Doppler to time intrauterine transfusion in red‐cell alloimmunization: a randomized trial. (5th February 2018) - Dodd, J. M.; Andersen, C.; Dickinson, J. E.; Louise, J.; Deussen, A.; Grivell, R. M.; Voto, L.; Kilby, M. D.; Windrim, R.; Ryan, G.; ,
ABSTRACT: Objectives: To evaluate whether Doppler measurement of middle cerebral artery peak systolic velocity (MCA‐PSV) for timing subsequent intrauterine transfusions (IUTs) in fetuses that had undergone one IUT for anemia secondary to red‐cell alloimmunization is non‐inferior to timing based on expected decrease in fetal hematocrit (Hct) or fetal hemoglobin level, without compromising infant hemoglobin at birth. Methods: This was an international, pragmatic multicenter randomized controlled trial. Women with a pregnancy complicated by fetal anemia secondary to red‐cell alloimmunization (due to any antibody alone or in combination), as indicated by the need to undergo a single IUT, were eligible for inclusion. Women were randomized to the determination of timing of further transfusion(s) by Doppler measurement of MCA‐PSV (MCA‐PSV Group), with a serial upward trend of values >1.5 multiples of the median considered indicative of the need for another IUT, or timing of transfusion by a decrease in fetal Hct (fetal Hct Group), with subsequent IUTs timed according to an estimated fall in fetal Hct of 1% per day or fetal hemoglobin of 0.3 g/dL per day, to maintain fetal hemoglobin level between 7 and 10 g/dL. The primary outcome was infant hemoglobin level measured at birth. Results: A total of 71 women were randomized, 36 to the MCA‐PSV Group and 35 to the fetal Hct Group. Median gestational age at randomization was 30.3 weeks, the majority of women were Caucasian and non‐smokers, 9.9% of women had Kell alloimmunization, and 14% of fetuses were hydropic at their first IUT. No statistically significant differences between the two treatment groups were observed with regard to mean hemoglobin levels at birth (MCA‐PSV Group, 10.36 ± 3.82 g/dL vs fetal Hct Group, 12.03 ± 3.14 g/dL; adjusted mean difference –1.56 g/dL (95% CI, –3.24 to 0.13 g/dL); P  = 0.070), or the number of IUTs performed after randomization (MCA‐PSV Group, 1.75 ± 1.79 vs fetal Hct Group 1.80 ± 1.32; adjusted relative risk 0.88 (95% CI, 0.61–1.26); P  = 0.474). There was no statistically significant difference between the two groups with respect to the risk of adverse infant outcomes related to alloimmunization or procedure‐related complications. Conclusion: Both Doppler measurement of MCA‐PSV and estimation of the decrease in fetal Hct or hemoglobin can be used to determine the timing of second and subsequent IUTs in fetuses with red‐cell alloimmunization. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.